Konsep Penerapan Pembiayaan Murabahah Pada bank Sumut Syariah KCP Rantau Prapat - Yusra Amelia Hsb; Nursantri Yanti (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This article analyzes the concepts of murabahah financing, this is done because there are still deviations in the implementation of murabahah financing, namely differences between the rules underlying murabahah financing and existing practices in the field. In this article, we compare the existing regulations with direct practical situations in the field involving several informants (practitioners and customers concerned) as well as with the support of several other supporting literature. The results of this research state that the application of murabahah in sharia banking practices is divided into three categories: The first type is consistent with muamalah fiqh. The second type is similar to the first type, but transfers ownership directly from the supplier to the customer, while the payment is made by the bank directly to the first seller/supplier and the third type is that the bank enters into a murabahah agreement with the customer, and at the same time represents (wakalah contract) to the customer for buy the things you want to buy yourself. Murabahah financing services for types 2 and 3 still need to be reviewed and re-evaluated because even though the financing is considered valid according to the Criminal Code law, it is still not valid according to Islamic law because the pillars of sale and purchase are still not fulfilled, namely ownership of the murabahah object. For this reason, researchers are developing the existing concept, namely a collaboration system between banks and suppliers.